PELAKSANAAN PENEGAKAN HUKUM REHABILITASI TERHADAP TINDAK PIDANA NARKOTIKA DI PENGADILAN NEGERI PANGKALAN KERINCI BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Sunggul Situmorang; Mukhlis R; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Act Number. 35 of 2009 on Narcotics as legal basis the statutory provisions governing the drug problem has been conceived and implemented, however, this drug related crime has not abated. It is precisely in the fact that the perpetrators of the crime is increasing, and the convict is not a deterrent and there is a tendency to repeat it again. It can be caused by the factors of sentences by a judge who does not give effect ataudeterrent impact against the perpetrators. Sentences by judges tend to be more emphasis on criminal sanctions commensurate with the deeds which if the offender. This paradigm is certainly not in accordance with the drug abuse problem, because not only is the drug addict criminals, but also as a victim.Therefore, Act Number. 35 of 2009 gives authority to judge drug addicts to examine cases in question may decide to undergo treatment and / or care. This study aimed to describe the legal provisions on sanctions for drug addicts as well as to determine the consideration the judge ruled the crime of drug addicts (study decision number: 187 / Pid.Sus / 2012 / PN. PLW). This study uses a literature review (libraryre search) by testing or examination of the products of the judiciary (court decision), namely Decision Number. 187/ Pid.Sus / 2013 / PN. PLW The analysis was conducted using qualitative research with normative approach. The use of methods and approaches are intended to obtain accurate data on the consideration of the judge ruled on the crime of drug addicts. From these results it can be concluded that the legal provisions on sanctions for drug addicts in Law Number. 35 of 2009 on Narcotics consists of two kinds of sanctions, ie sanctions and criminal sanctions measures (double track system). Criminal sanctions for drug addicts consists of the death penalty, imprisonment, and criminal penalties contained in the provisions of Article 116, Article 121, and Article 127.Keywords : Narcotics –– Case - Crime